1994
DOI: 10.1111/j.1476-5381.1994.tb13175.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin‐1‐induced myocardial ischaemia and oedema in the rat: involvement of the ETA receptor, platelet‐activating factor and thromboxane A2

Abstract: 1 The objectives of the present experiments were to assess the role of ETA receptors in mediating endothelin-1 (ET-1)-induced myocardial ischaemia and oedema and to study the involvement of plateletactivating factor (PAF) and thromboxane A2 (TxA2) in these actions of ET-1 in rats. 2 Intravenous bolus injection of ET-1 (0.1-2 nmol kg-') into anaesthetized rats induced ST segment elevation of the electrocardiogram in a dose-dependent manner without causing arrhythmias. ST segment elevation developed within 20-90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 65 publications
(99 reference statements)
0
23
0
Order By: Relevance
“…Given that ETB receptors predominate on vascular endothelial cells (Hosoda et al, 1991), ET-1 and IRL 1620 may induce gap formation directly via activation of ETB receptors or through release of secondary mediators such as platelet-activating factor (Filep et al, 1991) or thromboxane A2 (Filep et alt, 1994) or both. Release of secondary mediators may be mediated via ETA receptors as has been reported for the rat coronary circulation (Filep et al, 1994). Regardless of the mechanisms underlying gap formation, attenuation of ET-1-induced pulmonary vasoconstriction by FR 139317 or bosentan would lead to a reduction of capillary hydrostatic pressure, which, in turn, could result in a decrease in albumin extravasation.…”
Section: Discussionmentioning
confidence: 96%
“…Given that ETB receptors predominate on vascular endothelial cells (Hosoda et al, 1991), ET-1 and IRL 1620 may induce gap formation directly via activation of ETB receptors or through release of secondary mediators such as platelet-activating factor (Filep et al, 1991) or thromboxane A2 (Filep et alt, 1994) or both. Release of secondary mediators may be mediated via ETA receptors as has been reported for the rat coronary circulation (Filep et al, 1994). Regardless of the mechanisms underlying gap formation, attenuation of ET-1-induced pulmonary vasoconstriction by FR 139317 or bosentan would lead to a reduction of capillary hydrostatic pressure, which, in turn, could result in a decrease in albumin extravasation.…”
Section: Discussionmentioning
confidence: 96%
“…Endothelin is a potent constrictor of coronary arteries (15). Furthermore, administration of endothelin evokes ECG changes (10,16), similar to the clinical phenomenon of angina, especially variant angina. Yamamoto et al (10) reported that endothelin induced myocardial dysfunction in rabbits and fasudil prevented the occurrence of endothelin-induced ischemic myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, intracoronary or intravenous administration of ET-1 evokes ST segment elevations of the electrocardiogram, similar to the clinical phenomenon of Prinzmetal angina (Harada et al, 1993;Filep et al, 1994b) and enhances myocardial oedema formation in the rat (Filep et al, 1992;1994b).…”
Section: Introductionmentioning
confidence: 63%
“…Previous studies demonstrated that both intracoronary and intravenous administration of ET-1 elevates coronary resistance and induces ST segment elevations in rats, whereas arrhythmias could only be observed following intracoronary administration of the peptide (Harada et al, 1993;Filep et al, 1994b). It should be noted that following i.v.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation